Access and Control of Farm Households in the Management of Private Forest Resources - Eva Fauziyah (Balai Litbang Teknologi Agroforestry, Ciamis, 2018)
Differences in access of natural resources between men and women is one of the causes of gender unequality. This condition may have an impact on the lack of control, benefit, and participation of women on farming activities. This study aims to analyze the gender relation pattern in private forest management in Banyumas and Banjarnegara Districts.. Data were collected by using questionnaire, interview with farmer (men and women) and farmer groups with Socio Economic and Gender Analysis (SEAGA) instrument. Total respondents were 64 private forest farmers who were randomly selected. Data were analzsed by tabulation, percentage dan Equality adn Equity Index (EEI). The results showed that acces in private forest management were dominated by men e.g acces on land, crops cultivated, education, training, extension services, capital, credit, equipment, nursery, fertilization, cropping pattern, and pest and disease control. In contrary, women were more dominant in post harvest processing, and marketing activities. In Banyumas District, women control were dominant in marketing, while in Banjarnegara Distric, there was no dominance in both resources and stage activities but access and control were undertaken jointly between men and women in crops cultivation, watering, fertilization and marketing.The pattern of gender relations in general was more dominant both in terms of resources and the stages activies of private forest as indicated by EEI value tha is less than 0,5.